Learning Media Innovation: Development of Kompang Music Game to Enhance Local Cultural Knowledge in Early Childhood - Jamiyah, Siti; Utoyo, Setio (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to develop a traditional kompang music game model as a learning medium to enhance early childhood knowledge of local cultural arts at TK Ishlahul Ummah. This research addresses the gap in the availability of local culture-based learning media, which remain limited in early childhood education, despite their importance in supporting cultural identity and meaningful learning. Using a Research and Development (R&D) approach with the ADDIE model, the study identified children’s learning needs (Analysis), designed and developed the kompang game validated by experts (Design and Development, 4.9 very feasible), implemented the game with 40 children (Implementation), and evaluated its effectiveness (Evaluation). The effectiveness test, measured through pretest and posttest using a Paired Samples T-Test, showed a significant increase (p < 0.001) with a 30% improvement in children’s knowledge of local culture. The evaluation results also demonstrated that the media was well-received by teachers and learners, highlighting its practicality in classroom use. This study contributes theoretically by expanding the literature on local culture-based learning media in early childhood education and practically by providing an effective, enjoyable, and contextual alternative that can be integrated into early childhood curricula in various educational institutions.